2020
DOI: 10.1097/md.0000000000020901
|View full text |Cite
|
Sign up to set email alerts
|

High rate of burnout among residents under standardized residency training in a tertiary teaching hospital of middle China

Abstract: Burnout has been commonly observed in health care workers. Though research has been conducted involving burnout among doctors in China, few studies have focused on residents during standardized residency training (SRT). The professional status of the residents during SRT remains largely unclear. The present study was conducted in order to clarify the prevalence and potential risk factors of burnout in residents during SRT. An electronic questionnaire comprised 2 parts. The first part was designed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 29 publications
(36 reference statements)
1
26
3
Order By: Relevance
“…Doctors with more than 60 working hours per week and doing night shift would be expected to have a significantly much higher prevalence of burnout however in this study, however, there was no significant differences in the prevalence of burnout among them. The finding was contradicted with other studies done in various countries where long working hours and night shift were significantly associated with burnout [33][34][35] . The contradiction might be due to that those medical officers had already been able to cope with the long working hours and night shift as they have been experienced during their housemanship training years 36 .…”
Section: Resultscontrasting
confidence: 89%
“…Doctors with more than 60 working hours per week and doing night shift would be expected to have a significantly much higher prevalence of burnout however in this study, however, there was no significant differences in the prevalence of burnout among them. The finding was contradicted with other studies done in various countries where long working hours and night shift were significantly associated with burnout [33][34][35] . The contradiction might be due to that those medical officers had already been able to cope with the long working hours and night shift as they have been experienced during their housemanship training years 36 .…”
Section: Resultscontrasting
confidence: 89%
“…Nearly half (47.87%) of them were classified into ‘high’ and ‘very high’ turnover intention level, and 11.46% of them ‘often’ thought about quitting. The prevalence of high turnover intention among SRTP trainees (47.87%) was higher in our sample than that among residents in one teaching hospital in central China (37.8%), 35 and higher than that among psychiatry residents from a national sample (18.7%). 42 Compared with other Chinese physician populations, the average turnover intention score was lower than it was reported for general practitioners in Hubei (15.40, SD=3.43).…”
Section: Discussioncontrasting
confidence: 71%
“… 34 Another study conducted in a single tertiary hospital in central China reported their standardised residents to have a high rate of burnout, and 37.8% of them reported having the turnover intention. 35 However, these two studies did not examine the reasons and related factors for the turnover intention.…”
Section: Introductionmentioning
confidence: 99%
“…The present study analyzed the demographic and context data that could affect the performances of residents while ignoring factors related to burnout. A few studies on burnout indicated that it was universally existed in residency training [12,17,18] and might affect the residents' competency. It prompts us to pay attention on this issue and make some adjustments.…”
Section: Discussionmentioning
confidence: 99%